Penyuluhan dan Edukasi Pengendalian Hipertensi Melalui Pola Hidup Sehat bagi Masyarakat Desa Penembangan Kecamatan Cilongok Kabupaten Banyumas - Samodra, Galih; Santoso, Cahyo Budi; Fitriani, Artika Wina; Swandari, Mika Tri Kumala (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This Community Service Activity (PKM) aims to increase the knowledge and awareness of the Penembangan Village community, Cilongok District, Banyumas Regency regarding the importance of controlling hypertension through a healthy lifestyle. Hypertension is a non-communicable disease that is often ignored but has a serious impact on health. Through structured counseling and education, this activity provides information on risk factors, impacts, and strategies for preventing and managing hypertension. The methods used include lectures, interactive discussions, and direct practice related to the implementation of a healthy lifestyle such as a balanced diet, physical activity, and stress management. The results of this activity showed a significant increase in participants' knowledge and awareness of the importance of a healthy lifestyle in controlling hypertension. In addition, participants also showed a higher commitment to implementing a healthy lifestyle in their daily lives. It is hoped that this activity can be sustainable and become a model for similar programs in other areas, so that it can contribute to reducing the prevalence of hypertension and improving the quality of life of the community.